The Ukraine crisis: Unraveling the impacts and policy responses in low- and middle- income countries - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
The conflict in Ukraine is having widespread deleterious impacts on the economies and food systems of many low- and middle-income countries. Rising prices for food, fuel, and fertilizer have raised pressing concerns about food security and poverty. To better understand the risks in specific countries, IFPRI researchers have modeled the impacts of fuel, fertilizer, and food price shocks on GDP, employment, poverty, hunger, and diet quality in 19 countries in Africa and Asia, and examined the relative cost effectiveness of different policy interventions.